Isolation and Identification of Pathogenic Gram-Positive Bacteria from Egg Shell of Hen and to See Their Antimicrobial Susceptibility Pattern (Journal of Enam Medical College, 2016)
Background: Food-borne disease is a major public health problem affecting developed as well as developing countries. Inaccurately treated eggs can be one of its causes. So we designed this study to observe the possibility of transmission of pathogenic Gram-positive bacteria from market eggs to the community.Objectives: To identify different Gram-positive bacteria in eggs and to observe their antimicrobial susceptibility.Materials and Methods: This observational study was conducted in the department of Microbiology, Dhaka Medical College, Dhaka. Shells of 150 eggs collected from different markets of Dhaka city were tested. Bacteria were isolated and identified by culture and relevant biochemical tests.Results: Out of 150 egg shells, 120 (80%) yielded growth of different bacteria. Of them, Staphylococcus spp. were 80 (66.67%), Streptococcus spp. 8 (6.67%), Bacillus subtilis 20 (16.67%) and Bacillus cereus 12 (10%). Out of 80 Staphylococcus spp., 30 (25%) were Staphylococcus aureus and 50 (41.67%) were Staphylococcus saprophyticus. Most of the Gram-positive bacteria were sensitive to ciprofloxacin, ceftriaxone and imipenem. No MRSA and VRSA were found.Conclusion: It can be concluded from this study that Gram-positive bacteria from market eggs may be an important source of infection to the community.J Enam Med Col 2016; 6(1): 15-18